2019
DOI: 10.1002/jcb.29390
|View full text |Cite
|
Sign up to set email alerts
|

Decreased SPTLC1 expression predicts worse outcomes in ccRCC patients

Abstract: Objective Serine palmitoyltransferase, long chain base subunit 1 (SPTLC1) catalyzes the first step in sphingolipid synthesis and has been implicated in the progression of various cancers. However, its role in clear cell renal cell carcinoma (ccRCC) remains unclear. Here, we investigated the expression and prognostic value of SPTLC1 in ccRCC. Methods Three ccRCC patient cohorts were studied. ccRCC and adjacent normal kidney tissue samples were obtained from 183 patients at the Fudan University Shanghai Cancer C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…The incidence of RCC has increased steadily by about 1% per year, and the high mortality rate remains unchanged worldwide (18). Despite substantial improvements in available treatment options, the 5-year survival rate for advanced/metastatic RCC is <23% (19).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of RCC has increased steadily by about 1% per year, and the high mortality rate remains unchanged worldwide (18). Despite substantial improvements in available treatment options, the 5-year survival rate for advanced/metastatic RCC is <23% (19).…”
Section: Discussionmentioning
confidence: 99%
“…As a component of eukaryotic membranes, SLs has a variety of critical functions in the growth and development of embryos and the maintenance of normal physiology (53). In a clear cell renal cell carcinoma (ccRCC) study, bioinformatics analysis revealed that 10 genes, including SPTSSA, significantly coregulated ccRCC with SPTLC1, and the low expression of SPTLC1 was significantly correlated with the disease progression and poor prognosis of ccRCC (54). In addition, another gene ARSF, which is located in Xp22.3 with ARSD and ARSE, has significant homology and highly similar intron/exon structure.…”
Section: Discussionmentioning
confidence: 99%
“…It is the third most common cancer in the urinary system, and it has the maximum fatality rate. ccRCC is highly invasive, nearly 60% patients present metastasis at the procedure of diagnosis and therapy [19] . Meanwhile, metastatic cancer is not sensitive to chemotherapy and radiotherapy [20] .…”
Section: Discussionmentioning
confidence: 99%